Bilimsel Toplantı Duyuruları - Adli Tıp Uzmanları Derneği ATUD (Adli Tıp Bülteni, 2003)
The Chemistry of Explosives Course June 2003, Baltimore Presented by Computational Mechanics Associates. To be held in Albuquerque, NM. Computational Mechanics Associates PO Box 11314 (410) 532-3260 Fax: (410) 532-3261 74047.530@compuserve.com www .compmechanics .com Forensic Handwriting and Signature Examination: The Behavioral Approach Workshop July, 2003. The Orleans Hotel & Casino in Las Vegas, NV. American Board of Forensic Document Examiners. CONTACT: Derek L. Hammond US Army Criminal Investigation Laboratory 4553 N 2nd Street, Forest Park, GA 30297-5122 (404) 469-7044 Fax: (404) 469-7112 hammondd@usacil-acirs. army.mil Underwater Forensic Investigation Chaminade University of Honolulu in Honolulu, HI. CONTACT: Ron Becker, Chair Criminal Justice Department Chaminade University of Honolulu 3140 Waialae Avenue Honolulu, HI 96816-1578 rbecker@chaminade.edu 15th Annual Selected Topics in Child Abuse Course July,2003. Jesse Davis Special Programs Colby College, 4730 Mayflower Hill Drive Waterville, ME 04901-8847 (207) 872-3386 Fax: (207) 872-3383 summer@colby.edu www.colby.edu/spec.prog/cme.html Introduction to Bloodstain Pattern Analysis Course July 2003.University of North Texas in Denton, TX. CONTACT: Edward Hueske Forensic Training Coordinator, University of North Texas Police Academy Denton, TX 76203 (940) 565-4988 Fax: (940) 369-8663 xprtwit@aol.com International Academy of Legal Medicine XIX Congress 3-6 September, 2003 Universita degli Studi in Milan, Italy. CONTACT:OMNIA Meeting & Congress Torino, 29 00184 Roma (Italy) + 39 06 48 71 366 Fax: +39 06 48 15 339 info@omniameeting.com www.onmiameeting.com 3rd European Academy of Forensic Sciences Triennial Meeting 22-27 September, 2003, Istanbul -TURKEY İletişim: EAFS 2003 İstanbul Meeting Secreteriat. ODS Turizm Tel: +90 212 287 5800 Fax: +90 212 263 4581 www.eafs2003.enfsi.org eafs2003@enfsi.org Third European-American Intensive Course in Clinical and Forensic Genetics September 1-5, Zagreb, Croatia 2003Scientific Committee of EAICCFG dragan.primorac@st.tel.hr Tel/Fax. + + 385 1 370 4509 10. Ulusal Adli Tıp Günleri Adli Tıp Kurumu, 8-12 Ekim 2003. Aksu, Antalya İletişim: Adli Tıp Kurumu Başkanlığı34246, Esekapı, Cerrahpaşa hagritmis@hotmail.com International Society of Crimonology Thirdteenth World Congress of Criminology: Reducing Crime and promoting Justice: Challenges to Society, Policy and Practice 17-22 August, 2003, Rio de Janiero, Brasil Info: Prof. Tony Peters e-mail: tony.peters@law.kuleuven.ec.be. 19th European Congress of Pathology 6- 11 September, 2003. Slovenia Info: Tel: +386 1 2417135 e-mail: teja.alic@cd-cc.si 8th International Congress of Therapeutic Drug Monitoring and Clinical Toxicology 7- 11 September, 2003. Switzerland Info: ICTDMCT 2003 c/o Congress Plus GmbH, Haltingerstrasse 104, CH-4057 www.ictdmct2003.ch International Symposium on Forensic DNA Technologies 19-20 September, 2003. Münster, Germany Info: +49 -617 2679600 28th Congress of the International Academy of Law and Mental Health Sydney, Australia Information: Gail Fowler, Managinign Director, Capital Conferences, P.O. Box 253, Church Point, NSW 2105, Australia Tel: +61-2-99996577 Fax: +61-299995733 E-mail: syndey2003@ialmh.org http://www.ialmh.org/Sydney2003/ main.htm Association for Crime Scene Reconstruction Annual Workshop and Training Conference Oklahoma City, OK, USA Information: Tim Bevel, 2115 Westwod Drive, Norman, OK 73069, USA Tel: + 1-405-4474469 Fax: + 1-405-4474481 E-mail: tbevell@cox.net http://www.acsr.org 29th Annual Meeting of the Northeastern Association of Forensic Scientists Pittsfield, MA, USA Information: Jennifer F. Limoges, NEAFS President- Elect, New York State Police, Forensic Investigation Center, 1220 Washington Avenue, Bldg 30 Albany, NY 12226, USA Tel: +1-518-4570054 Fax: +1-518-4858502 E-mail: jlimoges@troopers.state.ny.us 41st Meeting of The International Association of Forensic Toxicologists (TIAFT 2003) Melmourne, Australia Information: Professor Olaf H.Drummer, Victorian Institute of Forensic Medicine, 57-83 Kavanagh Street, Southbank, Victoria, Australia 3006 Tel: +61 3 96844444 Fax: +61 3 96827353 E-mail: olaf@vifp.monash.edu.au 9th Australasian Conference on Child Abuse and Neglect Sydney, Australia Information: Jeanette Morgan, Conference Manager, department of Community Services, New South Wales Tel: + 61-2-92096229 Fax: + 61-2-92096233 E-mail: jeanette.morgan@community.nsw.gov.au http://www.community.nsw.gov.au/accan March-April 2004 (27-4) 17th International Symposium on the Forensic Sciences Wellington, New Zealand Information: Janet Simes Conference Manager, PO Box 41-016, Eastbourne, Wellington, New Zeland IV. Adli Bilimler Kongresi 28-30 Mayıs, 2004. İSTANBUL Adli Tıp Uzmanları Derneği iletişim: Dr. Coşkun Yorulmaz Î.Ü. Cerrahpaşa Tıp Fakültesi Adli Tıp AD e-posta: cosy@istanbul.edu.tr www.atud.org